Synthesis and applications of Perovskite in heavy metal ions removal-A brief perspective. (2022) - Jayanthi, G.; Sumathi, Sowrirajan; Andal, V.
Abstract: In the last few decades, Water Pollution by heavy metal waste has become a sober problem of concern. There are several conventional methods available for removing heavy metals such as chemical precipitation, flotation, ion-exchange, membrane filtration, reverse osmosis, electro dialysis, ultrafiltration, nanofiltration, coagulation, flocculation etc. Among the available methods adsorption is considered to be a suitable alternate due to its simplicity, effectiveness, cost-effective, versatility and safeness. Adsorption is an ideal method and adsorbent is one of the important factors which determine the efficiency of adsorption. This review throws an eloquent report on the removal of various heavy metals and its toxicity, using Perovskite as adsorbent and discusses the various factors which influence the adsorption process such as pH, initial concentration, temperature, adsorbent dosage, and contact time. In addition to it, associated Δ G ∙ (standard Gibbs free energy change), ΔH° (standard enthalpy change), ΔS° (standard entropy change), adsorption kinetics involved by pseudo-first-order, second order model and equilibrium adsorption by Langmuir and Freundlich isotherms are also debated. The efficiency of regeneration and reuse of the adsorbent by various methods are also summarized. This review will help the scientific community working on adsorption to choose a suitable adsorbent Perovskite for the heavy metal removal.